(untitled) (Research, Society and Development, 2020)
Spondias mombin L. is a fruit native to Brazil, there is a variation of the native species in the Cerrado. Its fruits are used in the production of food for the manufacture of jams, ice cream and juices and the leaves are used in folk medicine to treat inflammatory diseases.The objective was to analyze the thermodynamic behavior and properties of powdered cashew pulp at different temperatures during the desorption process. The analysis was performed using the dynamic-gravimetric method. Cajá fruits with water activity between 16.96 and 57.43 were used for thermodynamic analysis. Desorption of the thin layer of the fruit was observed at different temperatures (10, 20, 30 and 40 ° C) and water activity levels, ranging from 0.17 to 0.57, until the product reached equilibrium moisture content in the specified air condition. The thermodynamic properties of the cajá pulp were affected by the temperature and humidity content. The isokinetic theory can be proven for the desorption process and this is controlled by enthalpy. The desorption of water in cajá fruits is a non-spontaneous process.